Religion and Politics in the life of Arwa Al- Sulayhia: A Historical Analysis - Ramdane, Tahraoui; Souad, Merah (2018)
Throughout the history of Islam the status of Muslim woman was always a controversial topic, and a lot has been said about several forms of discrimination against her.  Nevertheless, the Islamic history preserved several examples of successful Muslim women who contributed to their societies and played an active social, economic, educational and political role in their respective local communities and nations.